How large could the public health impact of introducing recombinant zoster vaccination for people aged ≥50 years in five Latin American countries be?. Issue 1 (31st December 2023) - Han, Ru; Gomez, Jorge A.; de Veras, Bruna; Pinto, Thatiana; Guzman-Holst, Adriana; Nieto, Javier; van Oorschot, Désirée A. M.
ABSTRACT: This study aimed to: (1) estimate the disease burden of herpes zoster (HZ) and (2) assess the potential public health impact of introducing adjuvanted recombinant zoster vaccine (RZV) compared with no vaccination in adults aged ≥50 years in Argentina, Brazil, Mexico, Chile, and Colombia using the ZOster ecoNomic Analysis (ZONA) static multicohort Markov model. The model followed individuals aged ≥50 years from administration of RZV over their remaining lifetime. Inputs were based, most often, on local data. First dose coverage was assumed to be 35%, with 75% second dose compliance. It was predicted that without RZV, there would be 23, 558, 675 HZ cases, 6, 115, 981 post-herpetic neuralgia (PHN) cases, and 7, 058, 779 non-PHN complications in the five countries, but introducing RZV under assumed coverage could avoid 4, 583, 787 (19%) HZ cases, 1, 130, 751 (18%) PHN cases, and 1, 373, 419 (19%) non-PHN complications. Also, 10427, 504 (20%) doctor's office visits and 1, 630, 201 (19%) days of hospitalization could be averted in the three countries (Argentina, Brazil, and Mexico) with available input data. The numbers needed to be vaccinated to avoid one case of HZ were 9–10 across countries, and to avoid one case of PHN, 35–40. One-way sensitivity analyses showed that the input parameters with the largest impact on the estimated number of HZ cases avoided were first dose coverage, initial HZ incidence, and vaccine efficacy waning. In conclusion, the introduction of RZV for older adults in Latin America could greatly reduce the public health burden of HZ and reduce the related doctor visits and hospitalization days. Plain Language Summary: Why was the study done? Herpes zoster (HZ), commonly known as shingles or "culebrilla, " typically causes a painful, itchy rash on the trunk in older adults, and can result in long-term complications. It is difficult to study the lifetime burden of HZ due to follow-up time constraints. We therefore wanted to predict how many people could develop HZ as they age and how many cases of HZ could be avoided by introducing adjuvanted recombinant zoster vaccine (RZV) in people aged 50 years and older in five Latin American countries (Argentina, Brazil, Mexico, Chile, and Colombia). What did the researchers do and find? Using a mathematical model, we predicted that nearly 5 million of an estimated 24 million cases of HZ could be avoided by vaccinating 35% of older adults with RZV in the five countries. This vaccination approach would also avert various complications of HZ, including post-herpetic neuralgia (long-lasting pain at the rash site) and save doctor's office visits and hospitalizations for HZ. What do the results mean? Introducing RZV for older adults in Latin America – as is already the case in various other countries – could prevent a substantial proportion of HZ cases, leading to improved public health and less health care resource utilization. What is the objective influence on the wider field? In the absence of real-world data on the potential impact of RZV on HZ in Latin America, these predictions could help policymakers to assess the potential value of introducing RZV for older adults in Latin America. GRAPHICAL ABSTRACT: uf0001